2012
DOI: 10.1044/1059-0889(2012/12-0005)
|View full text |Cite
|
Sign up to set email alerts
|

Audiologists' Professional Satisfaction

Abstract: These results have implications for goal setting and planning within the profession and for audiologists' career choices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Private centers do offer facilities for audiological evaluation; however, they are not uniformly distributed across the country. [20]…”
Section: Challenges To Early Detection and Intervention Of Hearing Immentioning
confidence: 99%
“…Private centers do offer facilities for audiological evaluation; however, they are not uniformly distributed across the country. [20]…”
Section: Challenges To Early Detection and Intervention Of Hearing Immentioning
confidence: 99%
“…The assertion that audiology is a low-stress profession has also received support from studies that found that audiologists, overall, have low burnout and high job satisfaction (e.g., Blood et al, 2007Blood et al, , 2008Ferreira & Ferreira, 2015;Saccone & Steiger, 2012). Martin et al (1997) found, "audiologists are generally quite satisfied with their jobs and the tasks they perform" (p. 15).…”
mentioning
confidence: 99%
“…Martin et al (1997) found, "audiologists are generally quite satisfied with their jobs and the tasks they perform" (p. 15). More recently, Saccone and Steiger (2012) found, "despite a significant increase in the educational requirements for entry into the practice of audiology, there was no change in the overall professional satisfaction for respondents...when compared to the 1997 study " (p. 144).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been surveys from Western countries that probe into trends in professional practice, service delivery and consumer satisfaction [6][7][8][9][10][11]. MarkeTrak in the USA and EuroTrak in Europe are examples of such consumer directed surveys which have proved useful in understanding changes in practice, and its influence on patient outcomes [12,13].…”
Section: Introductionmentioning
confidence: 99%